Changes in Corticospinal Tract Consistency after Dry Needling in a Stroke Patient - Masoome Ebrahimzadeh; Noureddin Nakhostin Ansari; Iraj Abdollahi; Behnam Akhbari; Jan Dommerholt (Case Reports in Neurological Medicine)
Background. Dry needling (DN) is a technique employed to mitigate spasticity and enhance functionality in stroke patients. We report the impact of DN on both corticospinal tract (CST) consistency and wrist flexors spasticity of an individual affected by stroke. Case. The participant was a 57-year-old male who had experienced an ischemic stroke 9 months prior. The primary outcome measures included fractional anisotropy (FA), asymmetry FA (aFA), ratio FA (rFA), and Modified Modified Ashworth Scale (MMAS). Additionally, secondary outcomes encompassed wrist extension range of motion (ROM) and performance in the box and block test (BBT). These measurements were taken both before and after the administration of DN treatment. Results. After the application of DN, the mean FA of the ipsilesional CST increased from 0.35 to 0.39, concomitantly with a decline in aFA from 0.18 to 0.13. Notably, the rFA exhibited a pre-DN value of 0.69, which subsequently rose to 0.76 post-DN. Moreover, a significant reduction in MMAS scores was detected, from a score of “3” prior to DN application to a post-DN score of “1”. In terms of wrist mobility, both active and passive extension ROM exhibited favorable improvements, with an increase of 12° for active extension and 16° for passive extension. Furthermore, there was a substantial improvement in the BBT score, an indicator of manual dexterity, ascending from 12 to 24. Conclusion. Enhancements in CST consistency suggest it as a potential mechanism contributing to the observed improvements following DN in this stroke case.